2012
DOI: 10.2116/analsci.28.503
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Nickel Microspheres: Synthesis and Application for the Electrocatalytic Oxidation and Determination of Acyclovir

Abstract: Experimental Reagents and chemicalsAll other chemicals used in this work (otherwise those stated) were of analytical grade from Merck, and were used without further purification. Carbon micro-particles (graphite fine powder) with a particle size of less than 50 μm were obtained from Merck. Nafion solution was purchased from Sigma. All of the solutions were prepared by redistilled water. Acyclovir 2012 © The Japan Society for Analytical Chemistry † To whom correspondence should be addressed. Nickel microspheres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Based on the results obtained for G, Acy and Gan and although the molecules in the study did not show Nernstian behaviour, it can be assumed that 2e − /2H + (Scheme 1) are involved in the electrochemical process, consistent with that reported in the literature . In these studies, it has been reported that the oxidation mechanism of G and its pharmaceutical derivatives involves a deprotonation step and probably a breaking of the double bond in the imidazole ring (between the −N(7)=C(8)−) atoms) to give the final product 8‐oxoguanine .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Based on the results obtained for G, Acy and Gan and although the molecules in the study did not show Nernstian behaviour, it can be assumed that 2e − /2H + (Scheme 1) are involved in the electrochemical process, consistent with that reported in the literature . In these studies, it has been reported that the oxidation mechanism of G and its pharmaceutical derivatives involves a deprotonation step and probably a breaking of the double bond in the imidazole ring (between the −N(7)=C(8)−) atoms) to give the final product 8‐oxoguanine .…”
Section: Resultssupporting
confidence: 84%
“…Many works have been reported regarding the study of the electrochemical behaviour of Gan [18][19][20][21][22][23][24][25], Acy [26][27][28][29][30][31][32][33][34][35][36][37] and TG [38][39][40][41][42][43][44][45][46][47][48] upon a variety of unmodified and modified electrodes. These electrodes exhibited good responses in determining for pharmaceutical derivatives of guanine using differential pulse voltammetry, square wave stripping voltammetry, amperometry, potential scanning voltammetry and square wave voltammetry electrochemical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…This diffusional behavior was also observed for other nickel-based electrodes [33,34,38,39], due to diffusion of proton in the bulk of nickel oxide [44].…”
Section: Characterization Of Nickel Nanowrinklessupporting
confidence: 67%
“…In the past decades, there have been considerable attentions to the synthesis of metal nanostructures due to their different physical and chemical properties related to their similar large-scale ones, and potential applications in optical, electronic, catalytic and magnetic devices [27][28][29]. Among the metal nanostructures, nickel nanostructures have attracted much attention due to their applications in fabrication of sensors, biosensors, catalysts and conducting and magnetic materials [30][31][32][33][34][35][36][37].…”
Section: Hydrochlorothiazidementioning
confidence: 99%
“…This finding has been attributed to indirect effects of HSV suppression on HIV replication. Spectroscopy 2 chromatographic, [3][4][5][6][7] chemiluminescence, 8,9 spectrophotometric, [10][11][12] and voltammetric [13][14][15][16][17][18] analytical methods have been developed for the determination of acyclovir. With recent advancements in properties of the adsorptive stripping voltammetry, new methodologies have been developed for adenine, thymine, guanine, Adenosine triphosphate (ATP), DNA, and antiretroviral drugs determinations, employing alkaline solution with lower ionic strength as the supporting electrolyte.…”
Section: Introductionmentioning
confidence: 99%